2020
DOI: 10.1073/pnas.2020189117
|View full text |Cite
|
Sign up to set email alerts
|

Replisome bypass of a protein-based R-loop block by Pif1

Abstract: Efficient and faithful replication of the genome is essential to maintain genome stability. Replication is carried out by a multiprotein complex called the replisome, which encounters numerous obstacles to its progression. Failure to bypass these obstacles results in genome instability and may facilitate errors leading to disease. Cells use accessory helicases that help the replisome bypass difficult barriers. All eukaryotes contain the accessory helicase Pif1, which tracks in a 5′–3′ direction on single-stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 55 publications
3
48
0
Order By: Relevance
“…More recently, a series of elegantly designed in vitro templates was used to investigate how the E. coli replisome deals with more complex RNAP arrays as well as replication-R-loop collisions. Consistent with previous results [27][28][29][30], co-directional RNAP complexes imposed only transient blocks, whereas the HO orientation led to severe fork stalling, particularly when challenged with an array of multiple RNAPs. Altogether, these results provide insights into the robust enzymatic activities present at replisomes to unwind secondary structures and to displace both HO and CD RNAPs, allowing RNA takeover in the case of CD-TRCs (Figure 4B).…”
Section: Rnap Skipping and Reprimingsupporting
confidence: 91%
See 1 more Smart Citation
“…More recently, a series of elegantly designed in vitro templates was used to investigate how the E. coli replisome deals with more complex RNAP arrays as well as replication-R-loop collisions. Consistent with previous results [27][28][29][30], co-directional RNAP complexes imposed only transient blocks, whereas the HO orientation led to severe fork stalling, particularly when challenged with an array of multiple RNAPs. Altogether, these results provide insights into the robust enzymatic activities present at replisomes to unwind secondary structures and to displace both HO and CD RNAPs, allowing RNA takeover in the case of CD-TRCs (Figure 4B).…”
Section: Rnap Skipping and Reprimingsupporting
confidence: 91%
“…Interestingly, in vitro studies showed that replisomes bypass “naked” R-loops (in the absence of the transcription complex and other protein factors) in both orientations, suggesting that the genome-destabilizing effects of R-loops on replication fork stalling likely involve DNA–protein interactions such as the transcription complex or chromatin [ 26 ]. Consistently, it was shown that dCas9 protein-bound R-loop structures can arrest replisome progression, and bypass of this R-loop block relies on the monomeric Pif1 helicase in vitro [ 27 ].…”
Section: Trcs As a Potent Endogenous Source Of Dna Damage And Genomic Instabilitymentioning
confidence: 89%
“…Interestingly, CMG has been shown to be able to bypass DNA-protein crosslinks, even when the lesions are present on the translocating strand (Sparks et al 2019). This bypass activity is often aided by monomeric SF-I helicases and translocases that either help remove the block or promote CMG migration over the barrier (Yardimci et al 2012;Huang et al 2013;Sparks et al 2019;Schauer et al 2020). Surprisingly, SV40 LTag is able to actively navigate past large covalent protein-DNA blocks on the translocation strand without removing the adduct, suggesting that the ring briefly opens to continue unwinding past the block (Yardimci et al 2012).…”
Section: Roadblock and Damage Bypassmentioning
confidence: 99%
“…Indeed, loss of Rrm3 and Pif1 has an additive effect on pausing at tRNA genes (Osmundson et al, 2017;Tran et al, 2017). Accordingly, recombinant Pif1 supports polymerase and helicase-polymerase complex progression through barriers in vitro (Schauer et al, 2020;Sparks et al, 2020). Budding yeast Pif1 also promotes fork progression through G-quadruplex (G4) DNA structures (Paeschke et al, 2011) and migrating D-loops formed during break induced replication [BIR; (Wilson et al, 2013;Chung, 2014;Liu et al, 2021)].…”
Section: Accessory Helicases Displace Barriersmentioning
confidence: 99%
“…Budding yeast Pif1 also promotes fork progression through G-quadruplex (G4) DNA structures (Paeschke et al, 2011) and migrating D-loops formed during break induced replication [BIR; (Wilson et al, 2013;Chung, 2014;Liu et al, 2021)]. In vitro, Pif1 has been shown to promote bypass of dCas9, suggesting that it may act in general to remove both protein and R-loop blocks to replisome progression (Schauer et al, 2020). At the Fob1-rRFB, however, Rrm3 and Pif1 have confounding effects: whilst Rrm3 decreases pausing, as expected, Pif1 appears to have an unexplained opposite effect.…”
Section: Accessory Helicases Displace Barriersmentioning
confidence: 99%